Relationship between kinetic and kinematic measures of the countermovement jump and national weightlifting performance - Chavda, S.; Lake, J. P.; Comfort, P.; Bishop, C.; Joffe, S. A.; Turner, A. N. (Journal of Science in Sport and Exercise, 2025)
Purpose The association between vertical jump and weightlifting performance have been well established often using discrete performance measures such as jump height or peak power which provides little insight into temporal strategies. The purpose of this investigation was to identify currently unassessed temporal countermovement jump metrics and their reliability and relationship to national weightlifting performance.